Control-oriented modeling and experimental validation of a PEMFC generation system - Kunusch, Cristian (2011)
An experimentally validated control-oriented model that reproduces the most typical features of a laboratory proton exchange membrane fuel cell generation system, is presented in this paper. The proposed representation is a 7th order fully analytical nonlinear model of ordinary differential equations, primarily focused on the system gases dynamics. The complete model is developed following a modular procedure, combining theoretical modeling techniques and empirical analysis based on experimental data. The presented methods can be used as a general modeling guideline for control-oriented purposes, being possible to adapt to other fuel-cell-based systems with similar characteristics.